1999
DOI: 10.1074/jbc.274.34.24124
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of RNA Polymerase II Complexes Arrested by a Cyclobutane Pyrimidine Dimer in the Transcribed Strand of Template DNA

Abstract: We have characterized the properties of immunopurified transcription complexes arrested at a specifically located cyclobutane pyrimidine dimer (CPD) using enzymatic probes and an in vitro transcription system with purified RNA polymerase II (RNAP II) and initiation factors. To help understand how RNAP II distinguishes between a natural impediment and a lesion in the DNA to initiate a repair event, we have compared the conformation of RNAP II complexes arrested at a CPD with complexes arrested at a naturally oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 133 publications
(93 citation statements)
references
References 35 publications
5
86
0
2
Order By: Relevance
“…Although, these lesions are normally shielded by the arrested polymerase complex, 11 under certain conditions this may be displaced, allowing for photolyase access to CPD and, thus, RNA elongation in vitro. 21 In this work, photoreactivation in CHOphr cells efficiently restore RNA synthesis in UV-irradiated cells. Although this restoration decreases with time after UV (e.g.…”
Section: Discussionmentioning
confidence: 84%
“…Although, these lesions are normally shielded by the arrested polymerase complex, 11 under certain conditions this may be displaced, allowing for photolyase access to CPD and, thus, RNA elongation in vitro. 21 In this work, photoreactivation in CHOphr cells efficiently restore RNA synthesis in UV-irradiated cells. Although this restoration decreases with time after UV (e.g.…”
Section: Discussionmentioning
confidence: 84%
“…Most forms of damage targeted for repair by TCR also impede the translocation of RNAP complexes along DNA templates in vitro (6,8,33,35,36). Because bacteria, yeast, and mammals possess TCR, this mechanism may be evolutionarily conserved for efficient repair of DNA modifications that threaten genomic stability.…”
Section: Discussionmentioning
confidence: 99%
“…2). The constructs were transformed into the FЈ E. coli strain MV1184 for replication of the plus strand by the M13K07 phage (33). Plasmids containing dG, M 1 dG, or PdG in either the transcribed or nontranscribed strand were prepared by T4 DNA polymerase second-strand synthesis with the appropriate 18-mer as a primer.…”
Section: Construction Of Transcriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNAPII complex must be displaced and/or degraded in order for efficient repair because it shields the DNA lesion and prevents accessibility of NER proteins (reviewed in Licht et al, 2003;Fousteri et al, 2008). Several models have been proposed regarding how CSB rescues RNAPII complexes that are stalled at DNA lesions (Selby et al, 1997;Tornaletti et al, 1999), but the details of this process remains unclear. It has been suggested that CSB is involved in initiation of TCR through recognition of blocked RNAPII and binding to this complex, followed by recruitment of other NER proteins to the damaged site.…”
Section: The Role Of Csb In Various Cellular Processesmentioning
confidence: 99%